(untitled) (Annals of Medical Research, 2023)
Aim: People with chronic diseases have a higher rate of morbidity and mortality from SARS-CoV-2 infection. Unknown is how SARS-CoV-2 affects rare disease populations like Gaucher disease. The purpose of this research was to investigate the effects of SARS-CoV-2 infection has on Gaucher patients. The only study conducted in Turkey so far is this one. Materials and Methods: Patients with Gaucher disease were included in the study between August 2020 and September 2022. Patients diagnosed with Gaucher disease were questioned one-on-one to determine if they had come into contact with another person who had COVID-19 symptoms or another patient who had COVID-19. The patients were questioned and their answers were recorded regarding their GBA genotype, previous splenectomy history, whether or not they received treatment, and whether or not they had a SARS-CoV-2 test. Results: Eight of our patients reported having contact with someone who had COVID-19 infection or was suspected of having the infection, and in three of these cases (37.5%) the patient reported having at least one symptom of infection. Out of the 18 patients who were tested, 4 (22.2%) had a positive result. Positive test results were associated with more symptoms in patients (3.8 vs 0.3, p0.001) than negative test results. In Gaucher patients, symptoms or positive test results were not correlated with age, gender, BMI, comorbidity, genotype, previous splenectomy, or enzyme replacement therapy. All of our patients only received supportive care; none of them required intensive care or specialized treatment. Conclusion: Our research revealed that there was a low risk of serious side effects in other chronic patients following SARS-CoV-2 infection in Gaucher patients. In this regard, studies with larger case series are required.